Lipid responses to environmental perfluoroalkyl substance exposure in a Taiwanese Child cohort. (15th August 2021) - Lee, Sheng-Han; Tseng, Wei-Chen; Du, Zhi-Yi; Lin, Wan-Yu; Chen, Mei-Huei; Lin, Ching-Chun; Lien, Guang-Wen; Liang, Hao-Jan; Wen, Hui-Ju; Guo, Yue-Leon; Chen, Pau-Chung; Lin, Ching-Yu
Abstract: Although recent epidemiologic studies have focused on some of the health effects of perfluoroalkyl substance (PFASs) exposure in humans, the associations between PFASs exposure and the lipidome in children are still unclear. The purpose of this study was to assess lipid changes in children to understand possible molecular events of environmental PFASs exposure and suggest potential health effects. A total of 290 Taiwanese children (8–10 years old) were included in this study. Thirteen PFASs were analyzed in their serum by high-performance liquid chromatography-tandem mass spectrometry (LC-MS). MS-based lipidomic approaches were applied to examine lipid patterns in the serum of children exposed to different levels of PFASs. LC coupling with triple quadrupole MS technology was conducted to analyze phosphorylcholine-containing lipids. Multivariate analyses, such as partial least squares analysis along with univariate analyses, including multiple linear regression, were used to analyze associations between s exposure and unique lipid patterns. Our results showed that different lipid patterns were discovered in children exposed to different levels of specific PFASs, such as PFTrDA, PFOS, and PFDA. These changes in lipid levels may be involved in hepatic lipid metabolism, metabolic disorders, and PFASs-membrane interactions. This study showed that lipidomics is a powerful approach to identify critical PFASs that cause metabolite perturbation in the serum of children and suggest possible adverse health effects of these chemicals in children. Graphical abstract: Image 1 Highlights: Levels of PFOS, PFTrDA, and PFDA were associated with lipid perturbations in child serum. Lipid changes may be involved in metabolic disorder and membrane dysfunction. Lipidomics is a powerful tool to identify critical contaminants at environmental levels. Abstract : Lipidomic approaches in environmental studies are useful to identify critical perfluoroalkyl substances and suggest their potential health effects on children.